AN EVALUATION OF THE HUMAN RESOURCE PERFORMANCE OF PUBLIC HEALTH SERVICE UNIT: A CASE STUDY OF COMMUNITY HEALTH CENTERS IN BATAM - Syari, Arman; Suaduon, Jogie; Nugraha, Andika Prasetya; Yanti, Sri; Nurhatisyah, (International Journal of Psychosocial Rehabilitation, 2020)
Puskesmas is the most strategic "health service unit" in the health service system in Indonesia. Since the era of decentralization, and the effective implementation of the National Health Insurance (JKN) as the sole guarantor for Preventive, Curative and Rehabilitative diseases, the Puskesmas Unit has sought to meet service standards, especially personnel in the Public Health Efforts (UKM) section. The purpose of this research is to look at the effect of Innovative Work Behavior, Human Resource Competency, Self-Efficacy to Human Resource Performance Through Person-Job FIT, expected to be in line with the needs of the times. The population in this study was the Head of the Puskesmas, Structural Position and Functional section in the Batam City Puskesmas, totaling 185 respondents using the census method, used as the sample population. Data were analyzed using Structural Equation Model (SEM). The software used for structural analysis is AMOS version 23 of Arbuckle, and for descriptive studies using SPSS version 23. The results of the study indicate that Self-Efficacy is more prominent than other variables as the main formers of the Influence of Performance of Puskesmas HR in Batam City. By having the appropriate competence and coupled with confidence in the ability possessed to perform their duties, Employee Performance will increase.